Synthesis of ZnO Nanorods at Very Low Temperatures Using Ultrasonically Pre-Treated Growth Solution - Khairul Anuar Wahid, Khairul Anuar Wahid; Irfan Abdul Rahim, Irfan Abdul Rahim; Syafiqah Nur Azrie Safri, Syafiqah Nur Azrie Safri; Ahmad Hamdan Ariffin, Ahmad Hamdan Ariffin (Mdpi, 2023)
This paper investigates how the pre-treatment of the growth solution with ultrasonic energy affects the annealing temperatures and the growth temperatures of zinc oxide (ZnO) nanorods. The ultrasonic pre-treatment of the growth solution resulted in the successful growth of ZnO nanorods at a very low annealing temperature of 40 ◦C. The size and density of ZnO nanorods were found to increase proportionally with the increasing duration of pre-ultrasonic treatment, as indicated by characterisations performed with a scanning electron microscope (SEM). At an annealing temperature of 40 ◦C, coupled with ultrasonic waves, the SEM results showed that ZnO nanorods’ length and diameter increased by 37 and 25%. A similar pattern was also observed at an annealing temperature of 60 and 80 ◦C, where the length and diameter of ZnO nanorods increased. In addition, the conductivity and acidity of the aqueous solution that had been sonicated were measured. The results showed that solution conductivity and acidity increased as the ultrasonic treatment continued for longer periods. After 3 min of sonication, the final conductivity and acidity of the solutions were found to be 9164 µS/cm and 6.64, respectively. The results also indicated that the ultrasonic pre-treatment of the growth solution increased the zinc nutrient concentration, which would affect the formation of ZnO nanorods. In addition to the ultrasonic effect, the annealing temperature influenced the active nucleation sites essential to the ZnO nanorods’ expansion.